Biculturalism and Xenocentrism in TV Series Never Have I Ever Season 1 - Selvy Jessica; Rifka Pratama (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
Never Have I Ever is an American Television Series, scripted by Mindi Kaling, which relies both American and Indian life. The main character of the series, Devi Vishwakumar, have the desire to live as Americans in where she lives. On the other hand, her family tends to live in both cultures. The phenomena of biculturalism and xenocentrism may leads to some conflicts if they are not responded in a fine way. The aim of this paper is to discuss further about the the indication of bicultural family in the Devi family, and to analyze the indication of xenocentrist behavior in Devi Vishwakumar. Library research method is used by the writer in order to collect the necessary data, sociological approach in literature are used to analyze the data. The result of this study are the biculturalism in Devi's family is found on their clothing, food, and film and the xenocentrist behavior shown by Devi when she decides to eat beef, taunts her cousin who is too Indian, and tells her friend that Ganesh Puja is old and weird Indian festival.Keywords: biculturalism; xenocentrism; indian; american culture